Forest characteristics and population structure of a threatened palm tree Caryota obtusa in the karst forest ecosystem of Yunnan, China. (9th December 2021) - Tang, Cindy Q; Lu, Xia; Du, Min-Rui; Xiao, Shu-Li; Li, Shuaifeng; Han, Peng-Bin; Zeng, Jia-Le; Wen, Jian-Ran; Yao, Shi-Qian; Shi, You-Cai; Li, Yun-Fang; Peng, Ming-Chun; et al.
Abstract: Caryota obtusa of Arecaceae is a fascinating palm tree native to southwestern China, India, Myanmar, Thailand, Laos and Vietnam. It is an economically important and threatened species and appears as a canopy dominant in some karst areas in Yunnan. We aim to clarify the forest structure, species diversity, population status and regeneration dynamics of C. obtusa in the karst forest ecosystem of Yunnan, China. We established 56 vegetation plots dominated by C. obtusa in 10 counties of southern Yunnan. Based on the plot data, we analyzed the community stratification, floristic composition and C. obtusa 's population structure. We used questionnaires to interview local people and recorded the human activity history in C. obtusa -dominated forests. Caryota obtusa palm forests were distributed on limestone mountain slopes and gullies. There were seven forest community types. The stratification of each community included arborous layer, shrub layer and understory. The communities had rich species composition. For all the plots as a whole of each community type, Shannon–Wiener diversity index of either woody or herbaceous species ranged from 2.1 to 3.8. The diameter at breast height (DBH)-class frequency distribution of C. obtusa was a multimodal type. The regeneration was sporadic and dependent on intermediate natural disturbances. In the current population structure, a number of C. obtusa trees with small DBHs consisted mainly of the forest communities with no or a slight degree of human disturbances. Intensive human activities terribly hindered recruitment of C. obtuse, followed by the medium intensity of human activities.